Evaluating Health Insurance Inequality in Indonesia Using Concentration Curve and Index - Muryani (SCITEPRESS-Science and Technology Publications, Lda., 2017)
Equality in access to health services is one of main concerns in improving the public’s well-being. In Indonesia, the public administration has tried to achieve this equality by establishing National Health Insurance (NHI) in early 2014, replacing the older system of public health insurance. The data used in this study is the Indonesian Family Life Survey, which took place1 year after NHI implementation. This study has assessed the inequality in public and private health insurance for public and private health using a Concentration and Kakwani Index. Furthermore, the sample used was decomposed into a sub-sample to get more detailed information. This study found that there is some degree of inequality in public health insurance, but it is more pro-poor than private health insurance. However, there is evidence from the decomposed results that shows that there issome room for improving the inequality.